Smoking cessation using preference-based tools among socially disadvantaged smokers: study protocol for a pragmatic, multicentre randomised controlled trial - Maria Melchior; Brigitte Metadieu; Gladys Ibanez; Anne-Laurence Le Faou; Gilles Hejblum; Fabienne El-Khoury; Tarik El Aarbaoui; Mégane Héron (BMJ Open)
Introduction Many smoking cessation aids such as nicotine replacement treatments and e-cigarettes have been proven effective in aiding smoking cessation attempts. Encouraging smokers with low socioeconomic position (SEP) to choose their smoking aid tool based on their preferences, and giving that tool free of charge, might increase the odds of smoking cessation. This trial examines the effectiveness of the ‘STOP’ (Sevrage Tabagique à l’aide d’Outils dédiés selon la Préférence: Smoking cessation using preference-based tools), a preference-based smoking cessation intervention for smokers with low SEP.Methods and analysis The STOP study is a randomised, multicentre, controlled trial (RCT). Smokers with low SEP and wishing to quit will be randomised to either the intervention or the control group (standard care). Participants in the intervention group will be asked to choose between different types of nicotine substitutes (patches, inhalers, gum, tablets, etc) and/or an electronic cigarette which will be delivered free of charge to aid their smoking cessation attempt.The primary outcome will be smoking abstinence at 6 months after inclusion, defined as self-reported 7-day point prevalence of tobacco abstinence. Secondary outcomes include the total number of days of abstinence at 6 months after inclusion, 7-day point prevalence tobacco abstinence at 1 and 3 months after inclusion and number of relapses.The study will also include an economic evaluation, and a process evaluation using a mixed methods approach.Ethics and dissemination The study was approved by the ‘Île de France II’ Institutional Review Board on 8 September 2020 (CPP Île de France II; Ref No: 20.01.31.65528 RIPH2 HPS), and results will be published in a peer-reviewed journal.Trial registration number NCT04654585.